A study on anticorrosive property of phenolic components from Pachysandra terminalis against low carbon steel corrosion in acidic medium. Issue 5 (28th June 2019) - Chitra, Subramanian; Chung, Ill-Min; Kim, Seung-Hyun; Prabakaran, Mayakrishnan
Abstract : Purpose: The study aims to find new anticorrosive components from a plant source, namely, Pachysandra terminalis Sieb. et Zucc. ( P. terminalis ), a traditional medicinal shrub predominantly used by Tujia people. Design/methodology/approach: Because phenolic components from plants are known for its numerous values in several fields, the corrosion inhibitive ability of P. terminalis extract was analyzed by electrochemical studies (polarization, electrochemical impedance spectroscopy) and surface examination (by scanning electron microscopy [SEM], energy-dispersive X-ray spectroscopy [EDX] and atomic force microscopy [AFM]). Findings: The examination of total phenolic content (TPC), total flavonoids content (TFC) and individual phenols (UHPLC) showed the presence of 85.21 mg/g (TPC), 25.38 mg/g (TFC), protocatechuic acid (62.10 µg/g), gentisic acid (60.21µg/g), rutin (50.12 µg/g), kaempferol (46.58 µg/g) and p-Coumaric acid (42.35µg/g) . The polarization study shows that the maximum shift is (16 mV), imposing a mixed mode of inhibition, dominantly anodic. The surface morphology studies by SEM, EDX and AFM confirmed the adsorption of phytochemical components on the low carbon steel surface blocking the active sites. Originality/value: The study unveils the inhibitive nature of P. terminalis, preventing aggressive attack by 0.5 M HCl on low carbon steel. This also exhibits few phenols present in methanolic leaf extract which may be the role player of corrosion inhibition.